Da' Boom Enterprise / Mohamed Ali Md Arshad ... [et al.] - Md Arshad, Mohamed Ali; Norjahan Saleh, Azmi@Jimmy Shanley; Zainol Abidin, Azura; Md Radzi, Masni; Mohamad Noor, Mohd Shahnizam (2000)
We have on the whole agreed and decided to involve ourselves in this world of business which involves the sale of slaughter stock for venison, sale of breeding stock (live deer) and sale of velvet antlers and skins. As known, the activity of supplying deer stock is a relatively new field and has the potential to gain a large market. We got ourselves involved in this form of business, mainly due to the fact that we had high confidence that this business will be very profitable. This is because we feel that is of human nature to always demand for something new. This is where we hope the supply of deer will be able to fulfill the needs and wants of the society. The government has given it's full backing to the bumiputra community to get themselves involved in the breeding and supplying of deer's. Thus we feel that we are able to fulfill the call by the government. The type of deer that we will be breeding is of Cervus Timorensis species. It is breaded at an area in the Kuala Nerang district. We decided to choose that position because of the suitability of the area. The place is quite silent and far away from the daily activities of human beings. This is in fact quite good for the deer's, as they are quite sensitive to sounds and loud noises. Apart from that, the location that we have chosen to breed and supply the deer is quite near to our head office which is located at Alor Setar, thus making easier for the marketing of the deer's to our target market.